2019
DOI: 10.1097/meg.0000000000001667
|View full text |Cite
|
Sign up to set email alerts
|

Infection as a predictor of mortality in decompensated liver cirrhosis: exploring the relationship to severity of liver failure

Abstract: Background Infections are common in patients with liver cirrhosis and increase mortality. We explored the relationship between infection and liver dysfunction in their effects on mortality. Methods Single-center data on decompensated liver cirrhosis patients hospitalized between March 2014 and December 2017 (index period) were reviewed until death, liver transplantation or 31 December 2018. Infections were classified as community-acquired infection (CAi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…7). This is in agreement with the study from Croatia where infections increased 30-day mortality 2.3-times irrespective of the degree of liver failure [17]. The most prevalent infection site was the peritoneum (spontaneous bacterial peritonitis -SBP), which, together with respective proportions of the other sites, we consider to be a real reflection of the situation in our liver unit.…”
Section: Discussionsupporting
confidence: 92%
“…7). This is in agreement with the study from Croatia where infections increased 30-day mortality 2.3-times irrespective of the degree of liver failure [17]. The most prevalent infection site was the peritoneum (spontaneous bacterial peritonitis -SBP), which, together with respective proportions of the other sites, we consider to be a real reflection of the situation in our liver unit.…”
Section: Discussionsupporting
confidence: 92%
“…6 Interestingly, the observed mortality from COVID-19 is similar to that from bacterial infections as previously recorded in cirrhosis, and they likely share similar pathways in causing liver damage. 26,27 Hence, after contracting COVID-19 cirrhotic patients are at risk of becoming decompensated, with a high mortality as noted. According to a report from Asia, approximately 20% of patients with cirrhosis develop decompensation on the contraction of COVID-19, with a higher mortality among patients with a baseline Child-Turcotte-Pugh score >8.…”
Section: Discussionmentioning
confidence: 99%
“…This was also confirmed in a multicentric study from the United States ( n = 867 patients with CLD, of whom 134 had compensated and 93 decompensated cirrhosis) that found 2.9 times higher risk of death in decompensated patients as compared to those with compensated cirrhosis and non‐cirrhotic CLD 6 . Interestingly, the observed mortality from COVID‐19 is similar to that from bacterial infections as previously recorded in cirrhosis, and they likely share similar pathways in causing liver damage 26,27 . Hence, after contracting COVID‐19 cirrhotic patients are at risk of becoming decompensated, with a high mortality as noted.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils played an essential role in mediating inflammatory responses. Previous studies indicated infection increases mortality risk in decompensated liver cirrhosis patients [ 15 ]. As the protein synthesized specifically by the liver, serum albumin concentration was also influenced by inflammation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%